Setting Felicity Conditions and Deriving Logical Semantic Rules for the Commissive Speech Acts - Misbah. M.D. AL-Sulaimaan; Lubna M. Khoshaba (QALAAI ZANIST SCIENTIFIC JOURNAL, 2018)
Speech act can be defined as a verbal action that takes place in the reality. This means by uttering a speech act, the speaker "does" something with his word. The speaker performs an activity that brings about a change in the world of reality. As for the felicity conditions, they have been defined as the criteria that must be fulfilled if the speech act is to achieve its purpose. They are used to judge whether a certain utterance is a speech act, genuine speech act or none. This paper aims at setting some felicity conditions for the commissive speech acts category in the light of the illocutionary force components that set by Searle (1969 and 1983), Searle and Vanderveken (1985) as well as Vanderveken (1990 and 1994). It is hypothesized in this study that once felicity conditions are established for the commissive speech acts category, a set of logical semantic rules can be derived for determining the illocutionary forces indicating device of any commissive speech act. The procedure for achieving this paper will be based on the theoretical review of what Searle and Vanderveken have done in this area. The basic conclusions the study arrived at are setting some logical semantic rules for determining the illocutionary force indicating device of the